Penyuluhan tentang Zat Kimia Berbahaya yang Terkandung di dalam Kosmetik Bagi Kader PKK di Desa Doy Ulee Kareng Banda Aceh - Lidyawati; Rosa Mardiana; Dwi Putri Rejeki; Sasmiati Farach Dita; Verawati; Nurjannah; Irma Zarwinda; Elfariyanti; Fita Nelyza (Jurnal Mitra Pengabdian Farmasi, 2022)
Cosmetics are considered very important in today's life, not only women who use cosmetics but men also use it for their needs and lifestyle. There are also a lot of cosmetic products marketed by manufacturers, so people have to be more observant in choosing cosmetics that are safe to use, because not all producers pay attention to the safety quality of the ingredients of the products they produce, if people are wrong in choosing cosmetic products/using cosmetics that contain hazardous chemicals will cause health problems. The method used in this community service is counseling by providing knowledge about safe cosmetics, and prohibited and dangerous chemicals that are often used in cosmetics, then followed by a question and answer session. Furthermore, the PKK cadres were given a questionnaire which aims to determine the level of understanding of the PKK cadres after being given counseling. The activity was carried out in Doy Village, Ulee Kareng District, Banda Aceh. The results of the questionnaire show that 96 percent of PKK cadres understand how to choose safe cosmetics.